The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4tb00160e
|View full text |Cite
|
Sign up to set email alerts
|

Designed peptides for biomineral polymorph recognition: a case study for calcium carbonate

Abstract: With their unique ability for substrate recognition and their sequence-specific self-assembly properties, peptides play an important role in controlling the mineralization of inorganic materials in natural systems and in controlling the assembly of soft materials into complex structures required for biological functions. Here we report the use of an engineered heptapeptide that can differentiate between the crystalline anhydrous polymorphs of calcium carbonate. This peptide contains the positively charged amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…However, increasingly sophisticated methods for identifying the macromolecules involved in CaCO 3 biomineralisation suggest a more complex picture in which regulation is achieved using an array of molecules including glycosylated proteins, peptides, metabolites and polysaccharides 18 . Further, binding assays have shown that weakly acidic peptides can associate strongly with CaCO 3 1921 , and atomic force microscopy (AFM) and molecular dynamics (MD) simulations have demonstrated the strong binding of small hydroxyl-functionalised molecules 22,23 . This suggests potential roles for low-charge and basic molecules in controlling crystal properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasingly sophisticated methods for identifying the macromolecules involved in CaCO 3 biomineralisation suggest a more complex picture in which regulation is achieved using an array of molecules including glycosylated proteins, peptides, metabolites and polysaccharides 18 . Further, binding assays have shown that weakly acidic peptides can associate strongly with CaCO 3 1921 , and atomic force microscopy (AFM) and molecular dynamics (MD) simulations have demonstrated the strong binding of small hydroxyl-functionalised molecules 22,23 . This suggests potential roles for low-charge and basic molecules in controlling crystal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Complexing agents like citrate were suggested to affect early ACP formation 16,17 through the stabilization of ACP clusters whose subsequent aggregation can be promoted by the presence of non-collagenous proteins. 22 Therefore it was tempting to combine the bioactivity and osteoconductivity of vaterite nanoparticles with the flexibility and degradability of a hydrogel in order to develop a new bone grafting material. 18 Amorphous CaCO 3 (ACC) has been considered a potential inorganic precursor to induce the formation of bone minerals.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed a method to synthesise nonagglomerated and non-functionalised vaterite nanoparticles (Mugnaioli, Andrusenko, Schüler, et al, 2012;Schüler, Renkel, Hobe, et al, 2014;Schüler & Tremel, 2011). Vaterite, the least stable but most soluble crystalline polymorph of calcium carbonate forms positively charged nanoparticles that react and can be functionalised with carboxylate or phosphonate-bearing ligands (Schüler & Tremel, 2011).…”
mentioning
confidence: 99%